Molding resin composition and electronic component device
By adding calcium titanate particles and stress relaxant to the forming resin composition, the components are optimized, and the problems of high tangent of dielectric loss angle and insufficient resistance liquid in high-frequency environments are solved, thereby achieving low loss angle and high-efficiency signal Transported resin compositions suitable for sealing materials for high-frequency devices and packaging antennas.
Patent Information
- Application Number
- CN202380037623.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-10
- Filing Date
- 2023-06-09
- Publication Date
- 2024-12-20
AI Technical Summary
The resin composition for forming used in existing semiconductor packages has the problem of high dielectric loss tangent in high frequency environments, which leads to increased signal transmission loss and reduced communication efficiency. At the same time, the drug resistance to alkaline solutions is insufficient, making it difficult to Meet process requirements.
Using a resin composition for forming a forming process including epoxy resin, active ester compound, phenol hardener and calcium titanate particles, dielectric loss is reduced by optimizing the component ratio and adding stress relaxants such as indene-styrene-coumarone copolymer. Tangent and improve resistance to liquids.
The resin composition for forming with low dielectric loss tangent is achieved, which improves communication efficiency and maintains excellent drug resistance in high-frequency environments. It is suitable for sealing materials for high-frequency devices and packaging antennas.
Smart Images

Figure BDA0005111545070000071 
Figure BDA0005111545070000072 
Figure BDA0005111545070000081
Abstract
Description
Technical Field
[0001] The present disclosure relates to a molding resin composition and an electronic component device. Background Art
[0002] With the recent demand for higher functionality, thinner and smaller electronic devices, the high-density integration and mounting of electronic parts have been promoted, and the semiconductor packages used in these electronic devices have increased compared to the past, and the miniaturization has been promoted. Furthermore, the high frequency of radio waves used for communication in electronic devices is also being promoted.
[0003] In order to reduce the size of semiconductor packages and cope with high frequencies, high dielectric constant epoxy resin compositions for use in sealing semiconductor elements have been proposed (for example, see Patent Documents 1 to 3).
[0004] For example, Patent Documents 4 and 5 disclose a thermosetting resin composition containing an active ester resin as a curing agent for an epoxy resin, and the dielectric loss tangent of the cured product can be suppressed to be low.
[0005] [Prior art literature]
[0006] [Patent Document]
[0007] Patent Document 1: Japanese Patent Application Publication No. 2015-036410
[0008] Patent Document 2: Japanese Patent Application Publication No. 2017-057268
[0009] Patent Document 3: Japanese Patent Application Publication No. 2018-141052
[0010] Patent Document 4: Japanese Patent Application Publication No. 2012-246367
[0011] Patent Document 5: Japanese Patent Application Publication No. 2014-114352 Summary of the invention
[0012] [Problems to be solved by the invention]
[0013] As the material of the electronic parts such as the sealing semiconductor element, for example, the molding resin composition comprising epoxy resin, hardener and inorganic filler can be cited. As the molding resin composition, if the material with high dielectric loss tangent is used, the transmission signal is converted into heat due to the transmission loss, and the communication efficiency is easily reduced. Here, the amount of transmission loss generated by the heat conversion of the radio wave sent for communication in the dielectric body is expressed as the product of the square root of the frequency, the relative dielectric constant and the dielectric loss tangent. The transmission signal is easily converted into heat in proportion to the frequency. Especially in recent years, in order to cope with the increase of the number of channels accompanying the diversified information, the radio waves used in the communication are high-frequencyized. With regard to the viewpoint of reducing the transmission loss, a molding resin composition that can be formed with a hardened material with low dielectric loss tangent is sought.
[0014] In addition, when a molding resin composition is used in the production of a semiconductor package including electronic parts such as semiconductor elements, the molding resin composition needs to satisfy the process applicability in the production process of the package. For example, when making a semiconductor package, a redistribution layer is sometimes formed after the electronic parts are sealed with a molding resin composition, and in this case, an alkaline solution is used. However, there is room for improvement in the drug resistance of the sealing resin composition using an active ester compound as a hardener to an alkaline solution.
[0015] An object of the present disclosure is to provide a molding resin composition capable of molding a cured product having excellent chemical liquid resistance and a low dielectric loss tangent, and an electronic component device using the same.
[0016] [Technical means to solve the problem]
[0017] Specific means for solving the above-mentioned problems include the following aspects.
[0018] <1> A molding resin composition comprising:
[0019] Epoxy resin;
[0020] a hardener comprising an active ester compound and a phenol hardener; and
[0021] The inorganic filler includes calcium titanate particles.
[0022] <2> The molding resin composition according to <1>, wherein the content of the calcium titanate particles is 30% by volume to 60% by volume based on the total amount of the inorganic filler.
[0023] <3> The molding resin composition according to <1> or <2>, further comprising a stress relaxant.
[0024] <4> The molding resin composition according to <3>, wherein the stress relaxation agent comprises at least one of an indene-styrene-coumarone copolymer, a trialkylphosphine oxide, and a triarylphosphine oxide.
[0025] <5> The molding resin composition according to any one of <1> to <4>, wherein the phenol curing agent comprises an aralkyl-type phenol resin and a melamine-modified phenol resin.
[0026] <6> The molding resin composition according to any one of <1> to <5>, wherein the total content of the inorganic filler exceeds 55% by volume based on the total amount of the molding resin composition.
[0027] <7> The molding resin composition according to any one of <1> to <6>, which is used for a high-frequency device.
[0028] <8> The molding resin composition according to any one of <1> to <7>, which is used for sealing electronic components in high-frequency devices.
[0029] <9> The molding resin composition according to any one of <1> to <8>, which is used for encapsulating an antenna.
[0030] <10> An electronic component device, comprising:
[0031] Supporting members;
[0032] electronic components, disposed on the supporting member; and
[0033] A cured product of the molding resin composition according to any one of <1> to <9> for sealing the electronic component.
[0034] <11> The electronic component device according to <10>, wherein the electronic component includes an antenna.
[0035] [Effects of the Invention]
[0036] According to the present disclosure, there are provided a molding resin composition capable of molding a cured product having excellent chemical liquid resistance and a low dielectric loss tangent, and an electronic component device using the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] none DETAILED DESCRIPTION
[0038] In the present disclosure, the term "process" includes processes that are independent of other processes and processes that cannot be clearly distinguished from other processes as long as the purpose of the process is achieved.
[0039] In the present disclosure, in a numerical range represented by “to”, numerical values described before and after including “to” are respectively regarded as the minimum value and the maximum value.
[0040] In the numerical range recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range may also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range may also be replaced by the value shown in the embodiment.
[0041] In the present disclosure, each component may include a plurality of corresponding substances. When a plurality of substances corresponding to each component are present in the composition, unless otherwise specified, the content or content of each component refers to the total content or content of the plurality of substances present in the composition.
[0042] In the present disclosure, multiple types of particles corresponding to each component may be included. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component refers to the value for the mixture of the multiple types of particles present in the composition unless otherwise specified.
[0043] In the present disclosure, the “total content of silica particles and alumina particles” may be replaced by “the content of silica particles” or may be replaced by “the content of alumina particles”.
[0044] In the present disclosure, “the total of silica particles and alumina particles” may be replaced by “silica particles” or may be replaced by “alumina particles”.
[0045] Hereinafter, the method for implementing the present disclosure will be described in detail. However, the present disclosure is not limited to the following embodiments. In the following embodiments, the components (including component processes, etc.) are not required except for the cases specifically indicated. The same is true for numerical values and their ranges, which do not limit the present disclosure.
[0046] <Molding resin composition>
[0047] The molding resin composition disclosed herein includes: an epoxy resin; a hardener including an active ester compound and a phenol hardener; and an inorganic filler including calcium titanate particles.
[0048] As described above, in the case of the molding resin composition, excellent liquid resistance and low transmission loss are required in the hardened material after molding. From the viewpoint of suppressing transmission loss, it is desirable to achieve a low dielectric loss tangent. In the case of the molding resin composition disclosed in the present invention, the dielectric loss tangent of the hardened material can be reduced by using calcium titanate particles. Furthermore, by using a combination of an active ester compound and a phenol hardener as a hardener for an epoxy resin, a hardened material with excellent liquid resistance can be formed.
[0049] Furthermore, the molding resin composition of the present disclosure can be molded into a cured product having a lower dielectric loss tangent by using calcium titanate particles than when barium titanate or the like is used.
[0050] Hereinafter, each component constituting the molding resin composition will be described. The molding resin composition of the present disclosure contains an epoxy resin, a hardener, and an inorganic filler, and may contain other components as necessary.
[0051] (Epoxy resin)
[0052] The molding resin composition of the present disclosure contains an epoxy resin.
[0053] The type of epoxy resin is not particularly limited as long as it has an epoxy group in the molecule.
[0054] The molding resin composition may contain only one epoxy resin or two or more epoxy resins.
[0055] Specific examples of epoxy resins include: novolac-type epoxy resins (phenol novolac-type epoxy resins, o-cresol novolac-type epoxy resins, etc.) obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenolic compounds such as phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, and naphthol compounds such as α-naphthol, β-naphthol, and dihydroxynaphthalene with an aliphatic aldehyde compound such as formaldehyde, acetaldehyde, and propionaldehyde under an acidic catalyst to obtain a novolac resin, and then epoxidizing the novolac resin; and triphenylmethane-type phenol resins obtained by condensing or co-condensing the phenolic compound with an aromatic aldehyde compound such as benzaldehyde and salicylaldehyde under an acidic catalyst, and then epoxidizing the triphenylmethane-type phenol resins. triphenylmethane epoxy resin obtained by epoxidizing a phenol resin; a copolymerized epoxy resin obtained by epoxidizing a novolac resin obtained by co-condensing the phenol compound and the naphthol compound with an aldehyde compound under an acidic catalyst; a diphenylmethane epoxy resin as a diglycidyl ether of bisphenol A, bisphenol F, etc.; a biphenyl epoxy resin as a diglycidyl ether of an alkyl-substituted or unsubstituted biphenol; a styrene epoxy resin as a diglycidyl ether of a styrene-based phenol compound; an epoxy resin containing sulfur atoms as a diglycidyl ether of bisphenol S, etc.; an epoxy resin as a glycidyl ether of alcohols such as butanediol, polyethylene glycol, and polypropylene glycol; an epoxy resin as a diglycidyl ether of phthalic acid, isophthalic acid, glycidyl ester epoxy resins of glycidyl esters of polycarboxylic acid compounds such as phthalic acid and tetrahydrophthalic acid; glycidylamine epoxy resins obtained by replacing the active hydrogen bonded to the nitrogen atom of aniline, diaminodiphenylmethane, isocyanuric acid, etc. with a glycidyl group; dicyclopentadiene epoxy resins obtained by epoxidizing a co-condensation resin of dicyclopentadiene and a phenol compound; alicyclic epoxy resins such as diepoxy vinylcyclohexene, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 2-(3,4-epoxy)cyclohexyl-5,5-spiro(3,4-epoxy)cyclohexane-m-dioxane obtained by epoxidizing an olefin bond in the molecule; glycidyl ethers as p-xylene-modified phenol resins p-xylene modified epoxy resin; meta-xylene modified epoxy resin as glycidyl ether of meta-xylene modified phenol resin; terpene modified epoxy resin as glycidyl ether of terpene modified phenol resin; dicyclopentadiene modified epoxy resin as glycidyl ether of dicyclopentadiene modified phenol resin; cyclopentadiene modified epoxy resin as glycidyl ether of cyclopentadiene modified phenol resin; polycyclic aromatic ring modified epoxy resin as glycidyl ether of polycyclic aromatic ring modified phenol resin; naphthalene type epoxy resin as glycidyl ether of phenol resin containing naphthalene ring; halogenated phenol novolac type epoxy resin; hydroquinone type epoxy resin; trimethylolpropane type epoxy resin; linear aliphatic epoxy resin obtained by oxidizing olefin bonds using peracids such as peracetic acid;Aralkyl epoxy resins obtained by epoxidizing aralkyl phenol resins such as phenol aralkyl resins and naphthol aralkyl resins. Furthermore, epoxides of acrylic resins and the like can also be cited as epoxy resins. These epoxy resins can be used alone or in combination of two or more. ;
[0056] The epoxy resin preferably includes at least any one of an o-cresol novolac epoxy resin, a biphenyl aralkyl epoxy resin, and a biphenyl epoxy resin, and more preferably includes an o-cresol novolac epoxy resin and a biphenyl epoxy resin, or a biphenyl aralkyl epoxy resin and a biphenyl epoxy resin.
[0057] The epoxy equivalent (molecular weight / number of epoxy groups) of the epoxy resin is not particularly limited. From the viewpoint of balancing various properties such as moldability, reflow resistance, and electrical reliability, the epoxy equivalent of the epoxy resin is preferably 100 g / eq to 1000 g / eq, and more preferably 150 g / eq to 500 g / eq.
[0058] The epoxy equivalent of the epoxy resin is set to a value measured by a method in accordance with Japanese Industrial Standards (JIS) K 7236:2009.
[0059] When the epoxy resin is solid, the softening point or melting point of the epoxy resin is not particularly limited. From the viewpoint of moldability and reflow resistance, the softening point or melting point of the epoxy resin is preferably 40°C to 180°C, and from the viewpoint of operability during preparation of the molding resin composition, it is more preferably 50°C to 130°C.
[0060] The melting point or softening point of the epoxy resin is defined as a value measured by differential scanning calorimetry (DSC) or a method (ring and ball method) in accordance with JIS K 7234:1986.
[0061] From the viewpoints of strength, fluidity, heat resistance, moldability, etc., the mass ratio of the epoxy resin in the entire molding resin composition is preferably 0.5 mass % to 30 mass %, more preferably 2 mass % to 20 mass %, and further preferably 3.5 mass % to 13 mass %.
[0062] (Hardener)
[0063] The molding resin composition of the present disclosure contains a curing agent. The curing agent contains an active ester compound and a phenol curing agent.
[0064] The molding resin composition may contain only one type of active ester compound, or may contain two or more types of active ester compounds.
[0065] The molding resin composition may contain only one kind of phenol curing agent, or may contain two or more kinds of phenol curing agents.
[0066] -Active ester compound-
[0067] Here, the active ester compound refers to a compound having one or more ester groups reactive with an epoxy group in one molecule and having a curing effect on the epoxy resin.
[0068] When an active ester compound is used as a curing agent, the dielectric loss tangent of the cured product can be suppressed to be lower than when a phenol curing agent is used alone as a curing agent. The reason for this is presumably as follows.
[0069] In the reaction between epoxy resin and phenol hardener, secondary hydroxyl groups are generated. In contrast, in the reaction between epoxy resin and active ester compound, ester groups are generated instead of secondary hydroxyl groups. Since ester groups have lower polarity than secondary hydroxyl groups, the molding resin composition containing active ester compound as a hardener can suppress the dielectric loss tangent of the hardened material to be lower than the molding resin composition containing only a hardener that generates secondary hydroxyl groups as a hardener.
[0070] In addition, the polar groups in the cured product increase the water absorption of the cured product. By using an active ester compound as a curing agent, the concentration of polar groups in the cured product can be suppressed, and the water absorption of the cured product can be suppressed. Furthermore, by suppressing the water absorption of the cured product, that is, suppressing the content of H2O as a polar molecule, the dielectric loss tangent of the cured product can be suppressed to a lower level.
[0071] The type of active ester compound is not particularly limited as long as it has one or more ester groups that react with epoxy groups in the molecule. Examples of active ester compounds include phenol ester compounds, thiophenol ester compounds, N-hydroxyamine ester compounds, and esters of heterocyclic hydroxy compounds.
[0072] Examples of the active ester compound include ester compounds obtained from at least one of an aliphatic carboxylic acid and an aromatic carboxylic acid and at least one of an aliphatic hydroxyl compound and an aromatic hydroxyl compound. An ester compound using an aliphatic compound as a polycondensation component tends to have excellent compatibility with epoxy resins due to the presence of an aliphatic chain. An ester compound using an aromatic compound as a polycondensation component tends to have excellent heat resistance due to the presence of an aromatic ring.
[0073] As specific examples of active ester compounds, aromatic esters obtained by condensation reaction of aromatic carboxylic acids and phenolic hydroxyl groups can be cited. Among them, aromatic carboxylic acid components obtained by replacing 2 to 4 hydrogen atoms of aromatic rings such as benzene, naphthalene, biphenyl, diphenylpropane, diphenylmethane, diphenyl ether, diphenylsulfonic acid with carboxyl groups, monohydric phenols obtained by replacing 1 hydrogen atom of the aromatic ring with hydroxyl groups, and mixtures of polyhydric phenols obtained by replacing 2 to 4 hydrogen atoms of the aromatic ring with hydroxyl groups as raw materials are preferably used. Aromatic esters obtained by condensation reaction of aromatic carboxylic acids and phenolic hydroxyl groups. That is, aromatic esters having structural units derived from the aromatic carboxylic acid components, structural units derived from the monohydric phenols, and structural units derived from the polyhydric phenols are preferably used.
[0074] Specific examples of active ester compounds include phenol resins having a molecular structure in which a phenol compound is linked via an aliphatic cyclic hydrocarbon group, as described in Japanese Patent Laid-Open No. 2012-246367, and active ester resins having a structure obtained by reacting an aromatic dicarboxylic acid or a halide thereof with an aromatic monohydroxy compound. The active ester resin is preferably a compound represented by the following structural formula (1).
[0075] [Chemistry 1]
[0076]
[0077] In the structural formula (1), R 1 is a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a phenyl group; X is an unsubstituted benzene ring, an unsubstituted naphthalene ring, a benzene ring or a naphthalene ring substituted with an alkyl group having 1 to 4 carbon atoms, or a biphenyl group; Y is a benzene ring, a naphthalene ring, or a benzene ring or a naphthalene ring substituted with an alkyl group having 1 to 4 carbon atoms; k is 0 or 1; and n represents the average number of repetitions and is 0 to 5.
[0078] Specific examples of the compound represented by the structural formula (1) include the following exemplary compounds (1-1) to (1-10): t-Bu in the structural formula is a tert-butyl group.
[0079] [Chemistry 2]
[0080]
[0081] [Chemistry 3]
[0082]
[0083] Other specific examples of the active ester compound include a compound represented by the following structural formula (2) and a compound represented by the following structural formula (3) described in JP-A-2014-114352.
[0084] [Chemistry 4]
[0085]
[0086] In the structural formula (2), R 1 and R 2 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms, Z is an ester-forming structural site (z1) or a hydrogen atom (z2) selected from the group consisting of an unsubstituted benzoyl group, an unsubstituted naphthoyl group, a benzoyl group or naphthoyl group substituted with an alkyl group having 1 to 4 carbon atoms, and an acyl group having 2 to 6 carbon atoms, and at least one of Z is an ester-forming structural site (z1).
[0087] In the structural formula (3), R 1 and R 2 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms, Z is an ester-forming structural site (z1) or a hydrogen atom (z2) selected from the group consisting of an unsubstituted benzoyl group, an unsubstituted naphthoyl group, a benzoyl group or naphthoyl group substituted with an alkyl group having 1 to 4 carbon atoms, and an acyl group having 2 to 6 carbon atoms, and at least one of Z is an ester-forming structural site (z1).
[0088] Specific examples of the compound represented by the structural formula (2) include the following exemplary compounds (2-1) to (2-6).
[0089] [Chemistry 5]
[0090]
[0091] Specific examples of the compound represented by the structural formula (3) include the following exemplary compounds (3-1) to (3-6).
[0092] [Chemistry 6]
[0093]
[0094] As the active ester compound, commercially available products can also be used. As commercially available products of the active ester compound, active ester compounds containing a dicyclopentadiene-type diphenol structure include "EXB9451", "EXB9460", "EXB9460S", and "HPC-8000-65T" (manufactured by DIC Co., Ltd.); active ester compounds containing an aromatic structure include "EXB9416-70BK", "EXB-8", and "EXB-9425" (manufactured by DIC Co., Ltd.); active ester compounds containing acetylated products of phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Co., Ltd.); active ester compounds containing benzoylated products of phenol novolac include "YLH1026" (manufactured by Mitsubishi Chemical Co., Ltd.), etc.
[0095] The ester equivalent (molecular weight / number of ester groups) of the active ester compound is not particularly limited, but is preferably 150 g / eq to 400 g / eq, more preferably 170 g / eq to 300 g / eq, and even more preferably 200 g / eq to 250 g / eq from the viewpoint of balancing various properties such as formability, reflow resistance, and electrical reliability.
[0096] The ester equivalent of the active ester compound is set to a value measured by a method in accordance with JIS K 0070:1992.
[0097] -Phenol Hardener-
[0098] Specific examples of the phenol curing agent include: polyphenol compounds such as resorcinol, catechol, bisphenol A, bisphenol F, and substituted or unsubstituted biphenols; novolac-type phenol resins obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenol compounds such as phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, phenylphenol, aminophenol, and naphthol compounds such as α-naphthol, β-naphthol, and dihydroxynaphthalene with an aldehyde compound such as formaldehyde, acetaldehyde, and propionaldehyde in the presence of an acid catalyst; and polyphenol compounds such as polyphenols obtained by condensing or co-condensing the phenolic compounds with dimethoxy-p-xylene, bis(methoxymethyl)biphenyl, and the like. Synthetic aralkyl phenol resins such as phenol aralkyl resins and naphthol aralkyl resins; p-xylene-modified phenol resins and m-xylene-modified phenol resins; melamine-modified phenol resins; terpene-modified phenol resins; dicyclopentadiene-type phenol resins and dicyclopentadiene-type naphthol resins synthesized by copolymerizing the above-mentioned phenolic compounds with dicyclopentadiene; cyclopentadiene-modified phenol resins; polycyclic aromatic ring-modified phenol resins; biphenyl-type phenol resins; triphenylmethane-type phenol resins obtained by condensing or co-condensing the above-mentioned phenolic compounds with aromatic aldehyde compounds such as benzaldehyde and salicylaldehyde under an acidic catalyst; phenol resins obtained by copolymerizing two or more of these, etc. These phenolic hardeners may be used alone or in combination of two or more.
[0099] Among them, in the cured product of the molding resin composition, from the viewpoint of improving the adhesion (especially adhesion at high temperatures) to adherends such as electronic components and supporting members on which the electronic components are mounted, the phenol curing agent preferably contains an aralkyl phenol resin and a melamine-modified phenol resin, and more preferably contains a melamine-modified phenol resin.
[0100] The reactive group equivalent of the phenolic hardener (e.g., hydroxyl equivalent) is not particularly limited. From the perspective of balancing various properties such as formability, reflow resistance, and electrical reliability, the reactive group equivalent of the phenolic hardener is preferably 70 g / eq to 1000 g / eq, and more preferably 80 g / eq to 500 g / eq.
[0101] The hydroxyl equivalent of the phenol curing agent is set to a value measured by a method in accordance with JIS K 0070:1992.
[0102] The softening point or melting point of the curing agent is not particularly limited. From the viewpoint of moldability and reflow resistance, the softening point or melting point of the curing agent is preferably 40°C to 180°C, and from the viewpoint of workability during production of the molding resin composition, more preferably 50°C to 130°C.
[0103] The melting point or softening point of the curing agent is set to a value measured in the same manner as the melting point or softening point of the epoxy resin.
[0104] The equivalent ratio of the epoxy resin to the hardener (preferably the total of the active ester compound and the phenol hardener), that is, the ratio of the number of functional groups in the hardener to the number of functional groups in the epoxy resin (number of functional groups in the hardener / number of functional groups in the epoxy resin) is not particularly limited. From the perspective of suppressing the amount of each unreacted component, it is preferably set to a range of 0.5 to 2.0, and more preferably set to a range of 0.6 to 1.3. From the perspective of formability and reflow resistance, it is further preferably set to a range of 0.8 to 1.2.
[0105] The molar ratio of the ester group contained in the active ester compound to the reactive group contained in the phenol curing agent (ester group / reactive group in the phenol curing agent) is preferably 9 / 1 to 1 / 9, more preferably 8 / 2 to 2 / 8, and further preferably 3 / 7 to 7 / 3 from the viewpoint of chemical resistance to alkaline solutions.
[0106] From the viewpoint of achieving excellent flexural strength after curing of the molding resin composition and suppressing the dielectric loss tangent of the cured product to be low, the mass ratio of the active ester compound in the total amount of the active ester compound and the phenol curing agent is preferably 40 mass % to 90 mass %, more preferably 50 mass % to 80 mass %, and even more preferably 55 mass % to 70 mass %.
[0107] From the viewpoint of achieving excellent flexural strength after curing of the molding resin composition and suppressing the dielectric loss tangent of the cured product to be low, the mass ratio of the phenol curing agent in the total amount of the active ester compound and the phenol curing agent is preferably 10 mass % to 60 mass %, more preferably 20 mass % to 50 mass %, and even more preferably 30 mass % to 45 mass %.
[0108] In the case where the phenol curing agent includes a melamine-modified phenol resin, the content of the melamine-modified phenol resin is preferably 1% to 20% by mass relative to the total amount of epoxy resin, more preferably 2% to 15% by mass, and further preferably 3% to 10% by mass, and particularly preferably 3% to 8% by mass. The content of the melamine-modified phenol resin is more than 1% by mass relative to the total amount of epoxy resin, and in the cured product of the molding resin composition, there is a tendency to improve the adhesion (especially adhesion at high temperature) to adherends such as electronic parts and supporting members carrying the electronic parts. The content of the melamine-modified phenol resin is less than 20% by mass relative to the total amount of epoxy resin, and there is a tendency to suppress rapid gelation and ensure fluidity, and the content of the melamine-modified phenol resin is less than 8% by mass relative to the total amount of epoxy resin, and there is a tendency to suppress the dielectric loss tangent of the cured product.
[0109] When the phenol hardener includes a melamine-modified phenol resin and a phenol hardener other than the melamine-modified phenol resin (also referred to as other phenol hardeners; preferably an aralkyl-type phenol resin), the mass ratio of the melamine-modified phenol resin to the other phenol hardener, i.e., melamine-modified phenol resin: other phenol hardener, may be 1:1 to 1:30, 1:2 to 1:20, or 1:3 to 1:15.
[0110] When the molding resin composition contains an epoxy resin and a curing agent, the content of the curable resin other than the epoxy resin may be less than 5 mass %, 4 mass % or less, or 3 mass % or less relative to the total amount of the molding resin composition.
[0111] (Inorganic filler)
[0112] The molding resin composition of the present disclosure includes an inorganic filler containing calcium titanate particles.
[0113] The inorganic filler may contain other fillers besides the calcium titanate particles.
[0114] -Calcium titanate particles-
[0115] The shape of the calcium titanate particles is not particularly limited, and examples thereof include spherical, elliptical, and irregular shapes. The calcium titanate particles may also be crushed calcium titanate particles.
[0116] The calcium titanate particles may be surface-treated calcium titanate particles.
[0117] The calcium titanate particles may be a mixture of two or more fillers having different volume average particle sizes.
[0118] In the molding resin composition, from the viewpoint of the balance between dielectric loss tangent and fluidity, the mass ratio of calcium titanate particles to the total of epoxy resin and hardener (calcium titanate particles / total of epoxy resin and hardener) is preferably 1 to 25, more preferably 2 to 20, further preferably 3 to 15, and particularly preferably 4 to 12.
[0119] The volume average particle size of the calcium titanate particles is preferably 0.1 μm to 100 μm, more preferably 0.2 μm to 80 μm, further preferably 0.5 μm to 30 μm, particularly preferably 0.5 μm to 10 μm, and most preferably 0.5 μm to 8 μm.
[0120] The volume average particle size of calcium titanate particles can be measured as follows. The molding resin composition is placed in a crucible and placed at 800°C for 4 hours to ashed. The ash obtained can be observed using a scanning electron microscope (SEM), separated by shape and the particle size distribution is obtained based on the observed image, and the volume average particle size of the calcium titanate particles as the volume average particle size (D50) is obtained from the particle size distribution. In addition, the volume average particle size of the calcium titanate particles can also be obtained by measuring the laser diffraction / scattering particle size distribution measuring device (e.g., HORIBA, Ltd., LA920).
[0121] From the viewpoint of the balance between relative dielectric constant and dielectric loss tangent, the content of calcium titanate particles is preferably 30 to 60% by volume, more preferably 35 to 55% by volume, and still more preferably 40 to 50% by volume relative to the total amount of the inorganic filler.
[0122] -At least one of silica particles and alumina particles-
[0123] The inorganic filler preferably includes at least one of silica particles and alumina particles. The inorganic filler may include only one of silica particles and alumina particles, or may include both.
[0124] The silica particles and the alumina particles may be used alone or in combination of two or more. The silica particles and the alumina particles may be a mixture of two or more fillers having different volume average particle sizes.
[0125] The silica particles are not particularly limited, and examples thereof include fused silica, crystalline silica, and glass. The shape of the silica particles is not particularly limited, and examples thereof include spherical, elliptical, and irregular shapes. The silica particles may be crushed particles.
[0126] The silica particles may be surface-treated particles.
[0127] The shape of the alumina particles is not particularly limited, and examples thereof include spherical, elliptical, and irregular shapes. The alumina particles may be crushed particles.
[0128] The aluminum oxide particles may be surface-treated particles.
[0129] From the viewpoint of relative dielectric constant and thermal conductivity, the inorganic filler preferably contains alumina particles.
[0130] When the inorganic filler includes at least one of silica particles and alumina particles, from the viewpoint of low dielectric loss tangent, the total content of silica particles and alumina particles relative to the total amount of the inorganic filler is preferably 40 volume % to 70 volume %, more preferably 45 volume % to 65 volume %, and further preferably 50 volume % to 60 volume %.
[0131] The content rate (volume %) of silica particles, the content rate (volume %) of alumina particles, and the content rate (volume %) of calcium titanate particles relative to the total amount of the inorganic filler can be determined by the following method.
[0132] A thin slice sample of a cured product of a molding resin composition is photographed using a scanning electron microscope (SEM). An arbitrary area S is determined in the SEM image, and the total area A of the inorganic filler contained in the area S is obtained. Next, the elements of the inorganic filler are determined using SEM-EDX (scanning electron microscopy-energy dispersive X-ray spectrometer), thereby obtaining the total area B of specific particles such as silica particles, alumina particles, and calcium titanate particles contained in the total area A of the inorganic filler. The value obtained by dividing the total area B of the specific particles by the total area A of the inorganic filler is converted into a percentage (%), and the value is set to the content (volume %) of the specific particles relative to the total amount of the inorganic filler.
[0133] The area S is set to be sufficiently large relative to the size of the inorganic filler. For example, it is set to be large enough to contain 100 or more inorganic fillers. The area S may also be the total of a plurality of cut surfaces.
[0134] In the molding resin composition, from the viewpoint of the balance between dielectric loss tangent and fluidity, the mass ratio of the total amount of silica particles and alumina particles to the total amount of epoxy resin and hardener (the total amount of silica particles and alumina particles / the total amount of epoxy resin and hardener) is preferably 1 to 25, more preferably 2 to 20, further preferably 3 to 15, and particularly preferably 4 to 12.
[0135] The volume average particle size of the silica particles and the volume average particle size of the alumina particles are not particularly limited. The volume average particle size of the silica particles and the volume average particle size of the alumina particles are each independently preferably 0.2 μm to 100 μm, more preferably 0.5 μm to 50 μm. When the volume average particle size is 0.2 μm or more, the viscosity increase of the molding resin composition tends to be further suppressed. When the volume average particle size is 100 μm or less, the filling property of the molding resin composition tends to be further improved.
[0136] Regarding the volume average particle size of the silica particles and the volume average particle size of the alumina particles, the molding resin composition is placed in a crucible and placed at 800° C. for 4 hours to be ashed. The obtained ash can be observed by SEM, separated by shape and the particle size distribution can be obtained based on the observed image, and the volume average particle size of the silica particles and the volume average particle size of the alumina particles as the volume average particle size (D50) can be obtained from the particle size distribution. In addition, the volume average particle size of the silica particles and the volume average particle size of the alumina particles can also be obtained by measurement using a laser diffraction / scattering particle size distribution measuring device (e.g., LA920, manufactured by Horiba, Ltd.).
[0137] Regarding the volume average particle size of the silica particles and the volume average particle size of the alumina particles, from the perspective of the viscosity of the molding resin composition, they can each independently be greater than 3 μm, or greater than 5 μm, and from the perspective of the fluidity of the molding resin composition, they can each independently be greater than 10 μm, or greater than 20 μm.
[0138] When the inorganic filler includes at least one of silica particles and alumina particles, the total content of silica particles, alumina particles and calcium titanate particles may be 90 volume % or more, 95 volume % or more, or 100 volume % relative to the total amount of the inorganic filler.
[0139] -Other filling materials-
[0140] The inorganic filler may include other fillers besides silica particles, alumina particles, or calcium titanate particles.
[0141] The shape of the other filler is not particularly limited, and examples thereof include spherical, elliptical, and irregular shapes. In addition, the other filler may be a crushed filler.
[0142] Other fillers may also be surface-treated fillers.
[0143] The other fillers may be used alone or in combination of two or more. The other fillers may be a mixture of two or more fillers having different volume average particle sizes.
[0144] There is no particular limitation on the types of other fillers. Specifically, inorganic materials such as calcium carbonate, zirconium silicate, calcium silicate, silicon nitride, aluminum nitride, boron nitride, beryllium oxide, zircon, zircon, forsterite, steatite, spinel, mullite, titanium dioxide, talc, clay, and mica can be cited.
[0145] As other fillers, inorganic fillers having a flame retardant effect may also be used. Examples of inorganic fillers having a flame retardant effect include aluminum hydroxide, magnesium hydroxide, composite metal hydroxides such as composite hydroxides of magnesium and zinc, and zinc borate.
[0146] The content of other fillers may be 10% by volume or less, 5% by mass or less, or 0% by volume or less, based on the total amount of the inorganic filler.
[0147] Other fillers may include titanium compound particles other than calcium titanate particles. Examples of titanium compound particles other than calcium titanate particles include strontium titanate particles, barium titanate particles, potassium titanate particles, magnesium titanate particles, lead titanate particles, aluminum titanate particles, lithium titanate, and titanium oxide particles.
[0148] Among them, from the viewpoint of suppressing the dielectric loss tangent of the cured product to be low, the content of the barium titanate particles is preferably less than 1 volume %, more preferably less than 0.5 volume %, and further preferably less than 0.1 volume % relative to the total amount of the inorganic filler. That is, the inorganic filler preferably does not contain the barium titanate particles, or contains the barium titanate particles at the above content.
[0149] In addition, the total content of titanium compound particles other than calcium titanate particles may be less than 1 volume%, less than 0.5 volume%, or less than 0.1 volume% relative to the total amount of the inorganic filler. That is, the inorganic filler may not contain titanium compound particles other than calcium titanate particles, or may contain titanium compound particles other than calcium titanate particles in the above content.
[0150] The preferred ranges of the volume average particle diameter of other fillers are the same as the preferred ranges of the volume average particle diameter of the silica particles and the volume average particle diameter of the alumina particles.
[0151] -Total content and characteristics of inorganic fillers-
[0152] From the viewpoint of controlling the fluidity and strength of the cured product of the molding resin composition, the total content of the inorganic filler contained in the molding resin composition is preferably greater than 50% by volume, more preferably greater than 55% by volume, further preferably greater than 55% by volume and less than 90% by volume, and particularly preferably 60% to 80% by volume, relative to the total amount of the molding resin composition.
[0153] The content (volume %) of the inorganic filler in the molding resin composition can be determined by the following method.
[0154] A thin slice sample of a cured product of the molding resin composition is photographed using a scanning electron microscope (SEM). An arbitrary area S is determined in the SEM image, and the total area A of the inorganic filler contained in the area S is obtained. The value obtained by dividing the total area A of the inorganic filler by the area S is converted into a percentage (%), and the value is set as the content (volume %) of the inorganic filler in the molding resin composition.
[0155] The area S is set to be sufficiently large relative to the size of the inorganic filler. For example, it is set to be large enough to contain 100 or more inorganic fillers. The area S may also be the total of a plurality of cut surfaces.
[0156] Inorganic fillers may have a ratio deviation in the gravity direction when the molding resin composition is cured. In such a case, when photographing with SEM, the entire hardened material in the gravity direction is photographed, and the area S including the entire hardened material in the gravity direction is determined.
[0157] (hardening accelerator)
[0158] The molding resin composition of the present disclosure may contain a curing accelerator as needed. The type of the curing accelerator is not particularly limited, and can be selected based on the type of epoxy resin, the required properties of the molding resin composition, and the like.
[0159] Examples of the curing accelerator include diazabicycloolefins such as 1,5-diazabicyclo[4.3.0]nonene-5 (DBN) and 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), and cyclic amidine compounds such as 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 2-ethyl-4-methylimidazole, and 2-heptadecylimidazole; derivatives of the cyclic amidine compounds; and the cyclic amidine compounds or their derivatives. Phenol novolac salts; compounds with intramolecular polarization formed by adding maleic anhydride, 1,4-benzoquinone, 2,5-toluoquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone and other quinone compounds, compounds with π bonds such as diazonium methane, etc.; cyclic amidinium compounds such as tetraphenylborate of DBU, tetraphenylborate of DBN, tetraphenylborate of 2-ethyl-4-methylimidazole, and tetraphenylborate of N-methylmorpholine; pyridine, triethylamine, triethylenediamine, benzyl Tertiary amine compounds such as dimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol; derivatives of the tertiary amine compounds; ammonium salt compounds such as tetra-n-butylammonium acetate, tetra-n-butylammonium phosphate, tetraethylammonium acetate, tetra-n-hexylammonium benzoate, and tetrapropylammonium hydroxide; primary phosphines such as ethylphosphine and phenylphosphine, secondary phosphines such as dimethylphosphine and diphenylphosphine, triphenylphosphine, diphenyl(p-toluene)phosphine, tri(alkylphenyl)phosphine, tri(alkoxyphenyl)phosphine, tri(alkyl·alkoxyphenyl)phosphine, tri(dialkylphenyl)phosphine, tri(trialkylphenyl)phosphine, tri(tetraalkylphenyl)phosphine, tri(dialkoxyphenyl)phosphine, tri(trialkoxyphenyl)phosphine Phosphine, tri(tetraalkoxyphenyl)phosphine, trialkylphosphine, dialkylarylphosphine, alkyldiarylphosphine, trinaphthylphosphine, tri(benzyl)phosphine and other tertiary phosphine and other organic phosphine; phosphine compounds such as complexes of the organic phosphine and organic boron; compounds with intramolecular polarization formed by adding maleic anhydride, 1,4-benzoquinone, 2,5-toluoquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone, anthraquinone and other quinone compounds, diazonophenylmethane and other compounds with π bonds to the organic phosphine or the phosphine compound;The organic phosphine or the phosphine compound is reacted with 4-bromophenol, 3-bromophenol, 2-bromophenol, 4-chlorophenol, 3-chlorophenol, 2-chlorophenol, 4-iodophenol, 3-iodophenol, 2-iodophenol, 4-bromo-2-methylphenol, 4-bromo-3-methylphenol, 4-bromo-2,6-dimethylphenol, 4-bromo-3,5-dimethylphenol, 4-bromo-2,6-di-tert-butylphenol, 4-chloro-1-naphthol, 1-bromo-2-naphthol, 6- Compounds with intramolecular polarization obtained by reacting halogenated phenol compounds such as bromo-2-naphthol and 4-bromo-4'-hydroxybiphenyl and then undergoing a dehydrohalogenation process; tetraphenyl phosphonium and other tetrasubstituted phosphoniums, tetraphenyl phosphonium tetra-p-toluene borate and other tetraphenyl borate salts of tetrasubstituted phosphoniums; tetrasubstituted phosphonium compounds such as salts of tetrasubstituted phosphoniums and phenol compounds; salts of tetraalkyl phosphoniums and partial hydrolyzates of aromatic carboxylic anhydrides; phosphate betaine compounds; adducts of phosphonium compounds and silane compounds, etc. ;
[0160] The hardening accelerator may be used alone or in combination of two or more.
[0161] Among these, the curing accelerator is preferably a curing accelerator containing an organic phosphine. Examples of the curing accelerator containing an organic phosphine include phosphine compounds such as the organic phosphine and complexes of the organic phosphine and organic boron, and compounds having intramolecular polarization formed by adding a compound having a π bond to the organic phosphine or the phosphine compound.
[0162] Among these, particularly preferred hardening accelerators include trialkylphosphine and adducts of trialkylphosphine and quinone compounds; triphenylphosphine and adducts of triphenylphosphine and quinone compounds; adducts of tributylphosphine and quinone compounds; and adducts of tri-p-tolylphosphine and quinone compounds.
[0163] When the molding resin composition contains a hardening accelerator, the amount thereof is preferably 0.1 to 30 parts by mass, more preferably 1 to 15 parts by mass, relative to 100 parts by mass of the total of the epoxy resin and the hardener. If the amount of the hardening accelerator is 0.1 parts by mass or more relative to 100 parts by mass of the total of the epoxy resin and the hardener, there is a tendency to cure well in a short time. If the amount of the hardening accelerator is 30 parts by mass or less relative to 100 parts by mass of the total of the epoxy resin and the hardener, there is a tendency to obtain a molded product that is too fast in hardening and good.
[0164] (Stress Relaxant)
[0165] The molding resin composition disclosed in the present invention may include a stress relaxant. By including a stress relaxant, the warping deformation of the package and the generation of package cracks can be further reduced. As a stress relaxant, commonly used known stress relaxants (flexible agents) can be cited. Specifically, thermoplastic elastomers such as silicone, styrene, olefin, urethane, polyester, polyether, polyamide, and polybutadiene can be cited; indene-styrene-coumarone copolymers, etc.; triaryl phosphine oxides such as trialkylphosphine oxide and triphenylphosphine oxide; organic phosphorus compounds such as phosphate esters; rubber particles such as natural rubber (natural rubber, NR), acrylonitrile butadiene rubber (acrylonitrile butadiene rubber, NBR), acrylic rubber, urethane rubber, silicone powder, etc.; methyl methacrylate-styrene-butadiene copolymer (methacrylate methylstyrene butadiene, MBS), methyl methacrylate-silicone copolymer, methyl methacrylate-butyl acrylate copolymer, etc. have a core-shell structure. The stress relaxants may be used alone or in combination of two or more.
[0166] Examples of the silicone-based stress relaxant include silicone-based stress relaxants having an epoxy group, silicone-based stress relaxants having an amino group, and silicone-based stress relaxants obtained by polyether-modifying these. Silicone compounds such as silicone compounds having an epoxy group and polyether silicone compounds are more preferred.
[0167] From the viewpoint of dielectric loss tangent, the stress relaxation agent preferably includes at least one of an indene-styrene-coumarone copolymer, a trialkylphosphine oxide, and a triarylphosphine oxide. The stress relaxation agent may include at least one of an indene-styrene-coumarone copolymer and triphenylphosphine oxide.
[0168] When the molding resin composition contains a stress relaxation agent, the amount thereof is, for example, preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, based on 100 parts by mass of the total of the epoxy resin and the curing agent.
[0169] When the stress relaxation agent includes at least one of an indene-styrene-coumarone copolymer, a trialkylphosphine oxide, and a triarylphosphine oxide (preferably when it includes at least one of an indene-styrene-coumarone copolymer and triphenylphosphine oxide), the amount thereof is, for example, preferably 1 to 30 parts by mass, and more preferably 2 to 20 parts by mass, relative to 100 parts by mass of the total of the epoxy resin and the hardener.
[0170] The content of the silicone-based stress relaxant may be, for example, 2 parts by mass or less, or 1 part by mass or less, relative to 100 parts by mass of the total of the epoxy resin and the hardener. The molding resin composition may not contain the silicone-based stress relaxant. The lower limit of the content of the silicone-based stress relaxant is not particularly limited, and may be 0 parts by mass or 0.1 parts by mass.
[0171] From the viewpoint of dielectric loss tangent, the content of the silicone-based stress relaxation agent is preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 7% by mass or less, particularly preferably 5% by mass or less, and extremely preferably 0.5% by mass or less, relative to the total amount of the molding resin composition. The lower limit of the content of the silicone-based stress relaxation agent is not particularly limited, and may be 0% by mass or 0.1% by mass.
[0172] [Various additives]
[0173] The molding resin composition of the present disclosure may contain various additives such as coupling agents, ion exchangers, release agents, flame retardants, colorants, etc., in addition to the above-mentioned components. The molding resin composition of the present disclosure may contain various additives known in the art as needed, in addition to the additives exemplified below.
[0174] (Coupling agent)
[0175] The molding resin composition disclosed herein may include a coupling agent. From the viewpoint of improving the adhesion between the epoxy resin and the hardener and the inorganic filler, the molding resin composition preferably includes a coupling agent. As the coupling agent, there can be cited: silane compounds such as epoxy silane, mercapto silane, amino silane, alkyl silane, ureide silane, vinyl silane, disilazane, titanium compounds, aluminum chelate compounds, aluminum / zirconium compounds and other known coupling agents.
[0176] When the molding resin composition includes a coupling agent, the amount of the coupling agent is preferably 0.05 to 5 parts by mass, more preferably 0.1 to 2.5 parts by mass, relative to 100 parts by mass of the inorganic filler. If the amount of the coupling agent is 0.05 parts by mass or more relative to 100 parts by mass of the inorganic filler, there is a tendency for the adhesion with the frame to be further improved. If the amount of the coupling agent is 5 parts by mass or less relative to 100 parts by mass of the inorganic filler, there is a tendency for the moldability of the package to be further improved.
[0177] (Ion Exchanger)
[0178] The molding resin composition disclosed in the present invention may also contain an ion exchanger. From the viewpoint of improving the moisture resistance and high temperature storage characteristics of the electronic component device including the sealed electronic component, the molding resin composition preferably contains an ion exchanger. There is no particular limitation on the ion exchanger, and previously known ones can be used. Specifically, hydrotalcite compounds and hydroxides containing at least one element selected from the group consisting of magnesium, aluminum, titanium, zirconium and bismuth can be listed. The ion exchanger can be used alone or in combination of two or more. Among them, the hydrotalcite represented by the following general formula (A) is preferred.
[0179] Mg (1-X) Al X (OH)2(CO3) X / 2 ·mH2O……(A)
[0180] (0<X≦0.5, m is a positive number)
[0181] When the molding resin composition contains an ion exchanger, the content thereof is not particularly limited as long as it is a sufficient amount for capturing ions such as halogen ions. For example, the content of the ion exchanger is preferably 0.1 to 30 parts by mass, and more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the total of the epoxy resin and the hardener.
[0182] (Release Agent)
[0183] From the viewpoint of obtaining good demolding properties from the mold during molding, the molding resin composition disclosed in the present invention may also include a mold release agent. The mold release agent is not particularly limited, and previously known ones can be used. Specifically, ester waxes such as palm wax, montanic acid, stearic acid and other higher fatty acids, higher fatty acid metal salts, montanic acid esters, oxidized polyethylene, non-oxidized polyethylene and other polyolefin waxes, etc. can be listed. The mold release agent can be used alone or in combination of two or more.
[0184] When the molding resin composition contains a release agent, the amount thereof is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the total of the epoxy resin and the hardener. If the amount of the release agent is 0.01 parts by mass or more relative to 100 parts by mass of the total of the epoxy resin and the hardener, there is a tendency that sufficient demolding properties can be obtained. If it is 10 parts by mass or less, there is a tendency that better adhesion can be obtained.
[0185] (Flame Retardant)
[0186] The molding resin composition disclosed herein may also contain a flame retardant. The flame retardant is not particularly limited, and previously known ones can be used. Specifically, organic compounds or inorganic compounds containing halogen atoms, antimony atoms, nitrogen atoms, or phosphorus atoms, metal hydroxides, etc. can be cited. The flame retardant can be used alone or in combination of two or more.
[0187] When the molding resin composition contains a flame retardant, the amount thereof is not particularly limited as long as it is a sufficient amount to obtain the desired flame retardant effect. For example, the amount of the flame retardant is preferably 1 to 30 parts by mass, and more preferably 2 to 20 parts by mass, relative to 100 parts by mass of the total of the epoxy resin and the hardener.
[0188] (Colorant)
[0189] The molding resin composition disclosed herein may also contain a colorant. As the colorant, known colorants such as carbon black, organic dyes, organic pigments, titanium oxide, red lead, and iron oxide may be cited. The content of the colorant may be appropriately selected according to the purpose, etc. The colorant may be used alone or in combination of two or more.
[0190] (Method for preparing molding resin composition)
[0191] The preparation method of the molding resin composition is not particularly limited. As a general method, the following method can be cited: after the components of the prescribed blending amount are fully mixed by a mixer, etc., melt-kneading is performed by a grinding roll, an extruder, etc., and then cooled and crushed. More specifically, for example, the following method can be cited: the prescribed amount of the components is stirred and mixed, and kneaded by a kneader, a roll, an extruder, etc. preheated to 70°C to 140°C, and then cooled and crushed.
[0192] The molding resin composition disclosed in the present invention is preferably solid at normal temperature and pressure (for example, 25° C., atmospheric pressure). The shape of the molding resin composition when it is solid is not particularly limited, and examples thereof include powder, granules, and sheets. From the perspective of operability, the size and mass of the molding resin composition when it is in sheet form are preferably the size and mass that match the molding conditions of the package.
[0193] (Characteristics of molding resin composition)
[0194] The relative dielectric constant at 10 GHz of a cured product obtained by compression molding the molding resin composition of the present disclosure under the conditions of a mold temperature of 175° C., a molding pressure of 6.9 MPa, and a curing time of 600 seconds is, for example, 5 to 30. From the viewpoint of miniaturization of electronic parts such as antennas, the relative dielectric constant at 10 GHz of the cured product is preferably 6 to 25, more preferably 7 to 20, and even more preferably 8 to 17.
[0195] The relative dielectric constant is measured at a temperature of 25±3° C. using a dielectric constant measuring device (for example, Agilent Technologies, trade name “Network Analyzer N5227A”).
[0196] The dielectric loss tangent at 10 GHz of the cured product obtained by compression molding the molding resin composition disclosed in the present invention under the conditions of a mold temperature of 175°C, a molding pressure of 6.9 MPa, and a curing time of 600 seconds can be, for example, 0.015 or less. From the perspective of reducing transmission loss, the dielectric loss tangent at 10 GHz of the cured product is preferably 0.010 or less, more preferably 0.007 or less, and further preferably 0.005 or less. The lower limit of the dielectric loss tangent at 10 GHz of the cured product is not particularly limited, and for example, 0.001 can be cited.
[0197] The dielectric loss tangent is measured at a temperature of 25±3° C. using a dielectric constant measuring device (for example, Agilent Technologies, trade name “Network Analyzer N5227A”).
[0198] (Application of molding resin composition)
[0199] The molding resin composition disclosed herein can be applied to, for example, electronic component devices described below, and particularly to the production of high-frequency devices. The molding resin composition disclosed herein can also be used to seal electronic components in high-frequency devices.
[0200] In particular, in recent years, with the popularization of the fifth-generation mobile communication system (5G), the high-functionality and miniaturization of semiconductor packages (PKG) used for electronic parts devices have continued to develop. Moreover, with the miniaturization and high-functionality of PKG, the development of packaged antennas (Antenna in Package, AiP) as PKGs with antenna functions is also underway. In AiP, in order to cope with the increase in the number of channels accompanying the diversification of information, the radio waves used in communication are made high-frequency, and a low dielectric loss tangent is required in the sealing material.
[0201] As described above, the molding resin composition of the present disclosure can obtain a cured product having a low dielectric loss tangent. Therefore, among high-frequency devices, it is particularly suitable for antenna-in-package (AiP) applications in which an antenna disposed on a supporting member is sealed with the molding resin composition.
[0202] In an electronic component device including an antenna such as a package antenna, when an amplifier for power supply is provided on the side opposite to the antenna, heat is generated due to power supply. From the viewpoint of improving heat dissipation, the molding resin composition used in the manufacture of the electronic component device preferably contains alumina particles as an inorganic filler.
[0203] <Electronic components and devices>
[0204] The electronic component device disclosed herein includes a supporting member, an electronic component disposed on the supporting member, and a cured product of the molding resin composition that seals the electronic component.
[0205] As electronic component devices, there can be listed those in which electronic components (active components such as semiconductor chips, transistors, diodes, thyristors, etc., passive components such as capacitors, resistors, coils, antennas, etc.) are mounted on support members such as lead frames, conveyor tapes with completed wiring, wiring boards, glass, silicon wafers, organic substrates, and the electronic component area is sealed with a molding resin composition (for example, high-frequency devices).
[0206] The type of the supporting member is not particularly limited, and a supporting member generally used in the manufacture of electronic component devices can be used.
[0207] The electronic component may include an antenna, or may include an antenna and an element other than an antenna. The antenna is not limited as long as it functions as an antenna, and may be an antenna element or wiring.
[0208] In addition, in the electronic component device of the present disclosure, other electronic components may be arranged on the surface of the support member opposite to the surface on which the electronic components are arranged, as needed. Other electronic components may be sealed by the molding resin composition, may be sealed by other resin compositions, or may not be sealed.
[0209] (Method for manufacturing electronic component device)
[0210] The method for manufacturing an electronic component device disclosed herein includes: a step of arranging an electronic component on a supporting member; and a step of sealing the electronic component with the molding resin composition.
[0211] The method for implementing each of the steps is not particularly limited, and can be carried out by a general method. In addition, the types of support members and electronic components used in the manufacture of electronic component devices are not particularly limited, and support members and electronic components commonly used in the manufacture of electronic component devices can be used.
[0212] Examples of methods for sealing electronic components using the molding resin composition include low-pressure transfer molding, injection molding, compression molding, etc. Among these, the low-pressure transfer molding method is generally used.
[0213] [Example]
[0214] Hereinafter, the embodiment will be described in detail by way of examples, but the scope of the embodiment is not limited to these examples.
[0215] <Preparation of molding resin composition>
[0216] The molding resin compositions of Examples and Comparative Examples were prepared by mixing the following components at the blending ratios (parts by mass) shown in Tables 1 and 2. The molding resin compositions are solid at normal temperature and pressure.
[0217] In addition, in Table 1 and Table 2, blank columns mean that the components are not contained.
[0218] Tables 1 and 2 also show the content of the inorganic filler relative to the total amount of the molding resin composition (“content (volume %)” in the table).
[0219] In addition, CTO / total amount of inorganic filler in the table means the content ratio (volume %) of calcium titanate particles relative to the total amount of inorganic filler.
[0220] Epoxy resin 1: o-cresol novolac type epoxy resin, epoxy equivalent 200g / eq
[0221] Epoxy resin 2: biphenyl aralkyl type epoxy resin, epoxy equivalent 275g / eq
[0222] Epoxy resin 3: biphenyl type epoxy resin, epoxy equivalent 196g / eq
[0223] Hardener 1: Active ester compound, DIC Corporation, trade name "EXB-8"
[0224] Hardener 2: Phenol hardener, aralkyl type phenol resin, hydroxyl equivalent 170g / eq
[0225] Hardener 3: melamine-modified phenolic resin, reactive group equivalent 120 g / eq
[0226] Hardening accelerator: adduct of trialkylphosphine and 1,4-benzoquinone
[0227] Coupling agent: N-phenyl-3-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., trade name "KBM-573")
[0228] Release agent: montanic acid ester wax (Clariant Japan Co., Ltd., trade name "HW-E")
[0229] Colorant: Carbon black
[0230] Stress Relaxer 1: Indene-Styrene-Coumarone Copolymer
[0231] Stress Relaxer 2: Triarylphosphine oxide
[0232] Inorganic filler 1: calcium titanate particles, volume average particle size: 0.2 μm, shape: amorphous (CT-110)
[0233] Inorganic filler 2: Alumina particles, volume average particle size: 5.7 μm, shape: spherical
[0234] Inorganic filler 3: calcium titanate particles, volume average particle size: 4.0 μm, shape: amorphous
[0235] In addition, the volume average particle size of each of the inorganic fillers is a value obtained by the following measurement.
[0236] Specifically, first, an inorganic filler is added to a dispersion medium (water) in a range of 0.01 mass % to 0.1 mass %, and the mixture is dispersed for 5 minutes using a bath type ultrasonic cleaning machine.
[0237] 5 ml of the obtained dispersion was poured into a tank, and the particle size distribution was measured at 25° C. using a laser diffraction / scattering particle size distribution measuring apparatus (Horiba, Ltd., LA920).
[0238] The particle diameter of the cumulative value of 50% (volume basis) in the obtained particle size distribution was defined as the volume average particle diameter.
[0239] (Determination of gel time)
[0240] The gel time (GT) of the thermosetting resin composition was measured using a Curelastometer of JSR Trading Co., Ltd. 3 g of the thermosetting resin composition was measured at a temperature of 180° C. using a Curelastometer of JSR Trading Co., Ltd. The time until the torque curve rises was taken as the gel time (seconds). The results are shown in Tables 1 and 2.
[0241] (Evaluation of spiral flow (SF))
[0242] The thermosetting resin composition was molded by a transfer molding machine using a spiral flow measurement mold in accordance with EMMI-1-66 at a mold temperature of 180°C, a molding pressure of 6.9 MPa, and a curing time of 120 seconds, and the flow distance (cm) was determined. The results are shown in Tables 1 and 2.
[0243] (Adhesion Test)
[0244] Adhesion strength to copper (Cu)
[0245] By transfer molding machine, under the conditions of mold temperature 180 ℃, molding pressure 6.9MPa, and curing time 90 seconds, the molding resin composition is formed into the size of bottom surface diameter 3mm, upper surface diameter 3mm, and height 4mm on the copper plate. Then, the molded product is post-cured under the conditions of 175 ℃ and 5 hours. Thereafter, using a bonding tester (manufactured by Nordson Advanced Technology Co., Ltd., series 4000), the shear adhesion (MPa) is obtained at room temperature (25 ℃) or at a shear rate of 50μm / s while the temperature of the copper plate is maintained at 260 ℃. The evaluation criteria for adhesion are shown below. If it is A evaluation or B evaluation, the adhesion is good.
[0246] -Evaluation criteria for adhesion (25°C)-
[0247] A: Shear adhesion is 10.5MPa or more
[0248] B: Shear adhesion is 9.5 MPa or more and less than 10.5 MPa
[0249] C: Shear adhesion is less than 9.5MPa
[0250] -Evaluation criteria for adhesion (260°C)-
[0251] A: Shear adhesion is 1.0MPa or more
[0252] B: Shear adhesion is 0.6 MPa or more and less than 1.0 MPa
[0253] C: Shear adhesion is less than 0.6MPa
[0254] The results are shown in Tables 1 and 2.
[0255] (Drug resistance test)
[0256] The molding resin composition was loaded into a transfer molding machine, molded under the conditions of a mold temperature of 180°C, a molding pressure of 6.9 MPa, and a curing time of 90 seconds, and post-cured at 175°C for 6 hours to obtain a rod-shaped cured product (5mm×5mm×20mm). The rod-shaped cured product was used as a test piece and immersed in a mixed solution of dimethylsulfoxide (DMOS) / tetramethylammonium hydroxide (TMAH (tetramethylammonium hydroxide), 25% AQ.) = 92 / 8 (mass ratio) at 80°C for 1 hour. The mass before immersion was used as a reference, and the residual rate (mass %) was calculated using the following formula based on the mass of the test piece after 1 hour. The evaluation criteria for chemical liquid resistance are shown below. If it is A evaluation or B evaluation, the chemical liquid resistance is good.
[0257] Residual rate (mass %) = (mass after immersion (g) / mass before immersion (g)) × 100
[0258] -Evaluation criteria for chemical resistance-
[0259] A: Residual rate is 80% by mass or more
[0260] B: Residual rate: 30% to 80% by mass
[0261] C: The residual rate is more than 0 mass % and less than 30 mass %
[0262] D: Residual rate: 0 mass%
[0263] The results are shown in Tables 1 and 2.
[0264] (Determination of relative dielectric constant and dielectric loss tangent)
[0265] The molding resin composition was loaded into a transfer molding machine and molded under the conditions of a mold temperature of 180°C, a molding pressure of 6.9 MPa, and a curing time of 90 seconds. Post-curing was performed at 175°C for 6 hours to produce a rectangular test piece of 90 mm × 0.6 mm × 1.0 mm.
[0266] The relative dielectric constant (Dk) and dielectric loss factor (Df) of the test piece were measured at a frequency of 10 GHz using a cavity resonator (Kanto Electronics Application Development Co., Ltd.) and a network analyzer (Keysight Technologies, trade name "PNA N5227A") by the cavity resonance method at a temperature of 25±3°C. The results are shown in Tables 1 and 2.
[0267] [Table 1]
[0268]
[0269] [Table 2]
[0270]
[0271] As shown in Tables 1 and 2, the molding resin compositions of Examples can achieve both excellent chemical liquid resistance and low dielectric loss tangent.
[0272] Furthermore, in the molding resin compositions of Examples 1 to 4 and 7 to 12 using the curing agent 3, the evaluations of the adhesiveness (25° C.) and the adhesiveness (260° C.) were also good.
[0273] The entire disclosure of Japanese Patent Application No. 2022-094677 is incorporated into this specification by reference.
[0274] All documents, patent applications, and technical specifications described in this specification are incorporated herein by reference to the same extent as if each document, patent application, or technical specification was specifically and individually described as being incorporated by reference.
Claims
1. A molding resin composition comprising: Epoxy resin; a hardener comprising an active ester compound and a phenol hardener; and The inorganic filler includes calcium titanate particles.
2. The molding resin composition according to claim 1, wherein The content of the calcium titanate particles is 30 volume % to 60 volume % based on the total amount of the inorganic filler. The molding resin composition according to claim 1 , further comprising a stress relaxant.
4. The molding resin composition according to claim 3, wherein The stress relaxant includes at least one of an indene-styrene-coumarone copolymer, a trialkylphosphine oxide, and a triarylphosphine oxide.
5. The molding resin composition according to claim 1, wherein The phenol hardener includes an aralkyl type phenol resin and a melamine modified phenol resin.
6. The molding resin composition according to claim 1, wherein The total content of the inorganic filler exceeds 55% by volume based on the total amount of the molding resin composition. 7 . The molding resin composition according to claim 1 , which is used for a high-frequency device.
8. The molding resin composition according to claim 7, which is used for sealing electronic parts in high-frequency devices. 9 . The molding resin composition according to claim 7 , which is used for encapsulating an antenna.
10. An electronic component device comprising: Supporting members; Electronic components are arranged on the supporting member; as well as A cured product of the molding resin composition according to any one of claims 1 to 6 for sealing the electronic component.
11. The electronic component device according to claim 10, wherein: The electronic component includes an antenna.
Citation Information
Patent Citations
Thermosetting resin composition, cured product thereof, semiconductor sealing material, prepreg, circuit board and buildup film
JP2012246367A
Active ester resin, curable resin composition, cured product thereof, and printed wiring board
JP2014114352A
High-dielectric constant epoxy resin composition and semiconductor device
JP2015036410A
Resin composition and resin-sealed type semiconductor device
JP2018141052A
Metadata extraction program
JP2022094677A
